Massive Transfusion in Cardiac Surgery: The Impact of Blood Component Ratios on Clinical Outcomes and Survival - Delaney, Meghan; Stark, Paul C.; Suh, Minhyung; Triulzi, Darrell J.; Hess, John R.; Steiner, Marie E.; Stowell, Christopher P.; Sloan, Steven R. (Anesthesia and analgesia, 2017)
BACKGROUND:Cardiac surgery is the most common setting for massive transfusion in medically advanced countries. Studies of massive transfusion after injury suggest that the ratios of administered plasma and platelets (PLT) to red blood cells (RBCs) affect mortality. Data from the Red Cell Storage Duration Study (RECESS), a large randomized trial of the effect of RBC storage duration in patients undergoing complex cardiac, were analyzed retrospectively to investigate the association between blood component ratios used in massively transfused patients and subsequent clinical outcomes. METHODS:Massive transfusion was defined as those who had ≥6 RBC units or ≥8 total blood components. For plasma, high ratio was defined as ≥1 plasma unit:1 RBC unit. For PLT transfusion, high ratio was defined as ≥0.2 PLT doses:1 RBC unit; PLT dose was defined as 1 apheresis PLT or 5 whole blood PLT equivalents. The clinical outcomes analyzed were mortality and the change in the Multiple Organ Dysfunction Score (ΔMODS) comparing the preoperative score with the highest composite score through the earliest of death, discharge, or day 7. Outcomes were compared between patients transfused with high and low ratios. Linear and Cox regression were used to explore relationships between predictors and continuous outcomes and time to event outcomes. RESULTS:A total of 324 subjects met the definition of massive transfusion. In those receiving high plasma:RBC ratio, the mean (SE) 7- and 28-day ΔMODS was 1.24 (0.45) and 1.26 (0.56) points lower, (P = .007 and P = .024), respectively, than in patients receiving lower ratios. In patients receiving high PLT:RBC ratio, the mean (SE) 7- and 28-day ΔMODS were 1.55 (0.53) and 1.49 (0.65) points lower (P = .004 and P = .022), respectively. Subjects who received low-ratio plasma:RBC transfusion had excess 7-day mortality compared with those who received high ratio (7.2% vs 1.7%, respectively, P = .0318), which remained significant at 28 days (P = .035). The ratio of PLT:RBCs was not associated with differences in mortality. CONCLUSIONS:This analysis found that in complex cardiac surgery patients who received massive transfusion, there was an association between the composition of blood products used and clinical outcomes. Specifically, there was less organ dysfunction in those who received high-ratio transfusions (plasma:RBCs and PLT:RBCs), and lower mortality in those who received high-ratio plasma:RBC transfusions.